Ngarak Barong, Tradisi Lebaran Betawi dan Strategi Pemertahanan Budaya Masyarakat Etnis Betawi di Kampung Sawah Bekasi: Kajian Semiotika - Machdori Machdori; Tadjuddin Maknun; Ery Iswary (Universitas Nasional, 2022)
Ngarak Barong or ondel-ondel is the result of an ancient Betawi art called barongan, in the form of a pair of giant dolls in simple shapes, complete with a musical accompaniment team. At first, ondel-ondel was part of the people's sacred ritual activities which later became one of the icons of the city of Jakarta. Currently, ondel-ondel can still be found, both in the form of performing arts at wedding processions, government events in welcoming guests, as well as as processions to enliven Betawi Eid. In its development, the Ngarak Barong procession is still being carried out by the Betawi community, especially residents of the Kampung Sawah, Bekasi. But, along with the development of time, public awareness to continue to preserve local wisdom such as Barong has experienced a shift in values. Many found the Barong procession or ondel-ondel as a form of cultural defense, but it is more functioned for practical needs as a livelihood for singing so that Barong no longer has a sacred value as a cultural product that has a symbolic meaning. To see the meaning behind the signs of change, this qualitative research uses a semiotic approach. The relationship or relationship between the symbolic signs that exist in the structure and elements forming ondel-ondel is collaborated with the condition of society as the background and its impact in today's society to get meaning. Changes in the meaning and function of ondel-ondel in its constituent elements are produced and constructed as mental thoughts of users based on their form and context. The interpretation of the meaning of the cultural procession during the Ngarak Barong Betawi Lebaran procession will be different from the action of Ngarak Barong singing on the streets. There needs to be a policy given by the government to the impact of cultural shifts in the long term. Ngarak Barong atau ondel-ondel adalah hasil karya seni Betawi kuno bernama barongan, berupa sepasang boneka raksasa berbentuk sederhana, lengkap dengan tim musik pengiring. Pada awalnya ondel-ondel merupakan bagian dari aktivitas ritual sakral rakyat yang kemudian dijadikan sebagai salah satu ikon kota Jakarta. Saat ini ondel-ondel masih dapat ditemui, baik dalam bentuk seni pertunjukan pada prosesi pernikahan, acara pemerintahan dalam menyambut tamu, maupun sebagai prosesi arak-arakan dalam rangka memeriahkan lebaran Betawi. Dalam perkembangannya prosesi Ngarak Barong masih terus dilakukan oleh masyarakat Betawi, terutama warga masyarakat di Kampung Sawah, Bekasi. Namun seiring dengan perkembangan waktu, kesadaran masyarakat untuk terus melestarikan kearifan lokal seperti Barong telah mengalami pergeseran nilai. Banyak ditemukan arak-arakan Barong atau ondel-ondel sebagai bentuk pemertahanan budaya yang lebih difungsikan untuk kebutuhan praktis sebagai mata pencarian untuk mengamen sehingga Barong tidak lagi memiliki nilai kesakralan sebagai sebuah produk budaya yang memiliki makna simbolis. Untuk melihat makna di balik tanda-tanda perubahan yang terjadi, penelitian kualitatif ini menggunakan pendekatan semiotika. Hubungan atau relasi antar tanda simbolik yang ada pada struktur dan unsur-unsur pembentuk ondel-ondel dikolaborasikan dengan kondisi masyarakat sebagai latar belakang dan dampaknya dalam masyarakat saat ini untuk mendapatkan makna. Perubahan makna dan fungsi ondel-ondel pada unsur-unsur pembentuknya diproduksi dan dikonstruksi sebagai mental pemikiran penggunanya berdasarkan bentuk dan konteksnya. Interpretasi makna pada prosesi kebudayaan saat Ngarak Barong prosesi Lebaran Betawi akan berbeda dengan aksi Ngarak Barong mengamen di jalanan. Perlu adanya kebijakan yang diberikan oleh pemerintah terhadap dampak dari pergeseran budaya dalam jangka panjang.